ANALYZING THE ANTI-CORRUPTION POLICY IN MÉXICO (Andamios, Revista de Investigación Social, 2009)
This paper discusses some ideas of what the ethics of public servants should be, and contrasts the objectives and strategies outlined in the National Program to Combat Corruption by the federal government (Mexico, 2000-2006) with the objectives achieved at the end the administration and the place of Mexico in perceptions of corruption. The paper suggests that ethical development of public servants should be understood as a political issue, where the individual’s interest ought to be tuned to the institution he works for. The optimal functioning of the institution should thus be seen as a personal benefit.
Keywords: Corruption; policy ethics; administrative development; public service; Fox administration